Hidden depths: human costs of enforcement & compliance in no-take marine protected areas - Castelló y Tickell, S (2022)
Enforcement and compliance have been identified as key to the ecological effectiveness of no-take Marine Protected Areas (NTMPAs), which prohibit resource extraction in the marine realm. However, the human costs of abiding by NTMPAs have received little attention in comparison to the ecological benefits. As coverage of NTMPAs continues to rise worldwide, understanding human costs is important to the successful establishment and management of social relations around MPAs. Using key informant interviews and an online survey, this study identifies 18 human costs of compliance and enforcement and analyses their prevalence in time and space, as well as providing some suggested approaches to mitigating these costs. Results reveal transparency and communication in the establishment and management of NTMPAs, including engagement and education of local communities and training of enforcement officers, are key to mitigating the human costs of compliance and enforcement felt by enforcers and illegal and legal resource users.